Overview of Monetary Policy in the Nepalese Context - Ghimire, Ramesh (Economic Journal of Nepal, 2006)
Monetary policy is one of the most important policies to manage aggregate demand. Like other policies, the primary objectives of monetary policy to attain the macro economic goal or objectives such as stability, growth, full employment, favorable balance of payment and so on. Before liberalization, Nepal Rastra Bank followed direct monetary instruments such as interest rate, margin rate, statutory reserve requirements (SLR), and so on. However, after economic liberalization, indirect instruments such as cash reserve ratio, open market operation and bank rate have been used. These instruments first affect the aggregate demand and thereby it affects real sector variables such as price level, income, employment, output, and so on. But in Nepalese case, like other policies, monetary policy has not been effective to achieve its goals or objectives because price level is not explained by money supply alone. This present paper has made an attempt to overview the impact of monetary policy in terms of some macroeconomic indicators such as price level, economic growth, balance of payment and equity.Economic Journal of Nepal Vol.29(1) 2006 pp.54-60